Nasopharyngolaryngoscopy in the Diagnosis of Various Pathologies of the Larynx in a Tertiary Care Hospital. - Shrestha, Krishna Sundar; Shrestha, Bikash Lal; Pokharel, Monika; Dhakal, Ashish (Med Phoenix, 2022)
Introduction: Laryngeal disorders are frequently encountered in ENT practice. Nasopharyngolaryngoscopy is an outpatient department procedure that is used for the diagnosis and management of laryngeal disorders. The objective so the study was to study the prevalence of different laryngeal disorders by the use of Nasopharyngolaryngoscopy as an outpatient department procedure in ENT. Materials and Methods: A hospital-based prospective and analytical study was conducted in the department of ENT at Dhulikhel hospital, Kathmandu University Hospital during the period of 2 years. A total of 132 patients, who had various laryngeal symptoms and underwent NPL were included in this study. A careful and detailed history and clinical examination of the patients was done. Data were recorded and analyzed. Results A total of 132 patients with various laryngeal symptoms underwent Nasopharyngolaryngoscopy. Among them, 54.5% (72) were male and 45.5% (60) were female. The age range was from 18-84 years. The most common laryngeal disorder observed was Laryngopharyngeal reflux disease, followed by chronic laryngitis, true vocal cord nodule, and true vocal cord polyp. Conclusion Nasopharyngolaryngoscopy is a safe outpatient department procedure that is helpful for the diagnosis and management of various laryngeal disorders.